Dihydrogen‐Driven NADPH Recycling in Imine Reduction and P450‐Catalyzed Oxidations Mediated by an Engineered O2‐Tolerant Hydrogenase. Issue 19 (10th August 2020) - Preissler, Janina; Reeve, Holly A.; Zhu, Tianze; Nicholson, Jake; Urata, Kouji; Lauterbach, Lars; Wong, Luet L.; Vincent, Kylie A.; Lenz, Oliver
Abstract: The O2 ‐tolerant NAD + ‐reducing hydrogenase (SH) from Ralstonia eutropha ( Cupriavidus necator ) has already been applied in vitro and in vivo for H2 ‐driven NADH recycling in coupled enzymatic reactions with various NADH‐dependent oxidoreductases. To expand the scope for application in NADPH‐dependent biocatalysis, we introduced changes in the NAD + ‐binding pocket of the enzyme by rational mutagenesis, and generated a variant with significantly higher affinity for NADP + than for the natural substrate NAD +, while retaining native O2 ‐tolerance. The applicability of the SH variant in H2 ‐driven NADPH supply was demonstrated by the full conversion of 2‐methyl‐1‐pyrroline into a single enantiomer of 2‐methylpyrrolidine catalysed by a stereoselective imine reductase. In an even more challenging reaction, the SH supported a cytochrome P450 monooxygenase for the oxidation of octane under safe H2 /O2 mixtures. Thus, the re‐designed SH represents a versatile platform for atom‐efficient, H2 ‐driven cofactor recycling in biotransformations involving NADPH‐dependent oxidoreductases. Abstract : By protein engineering, we converted the NAD + binding pocket of an O2 ‐tolerant [NiFe]‐hydrogenase into a NADP + binding pocket. The resulting biocatalyst supported H2 ‐dependent NADPH recycling in coupled enzyme reactions involving imine reductase and P450 monoxygenase. The modified hydrogenase mediates atom‐efficient cofactor recycling in challenging biotransformations with oxidoreductases that depend on O2 and NADPH as co‐substrates.